Strain-Specific Neutralizing Antibody Responses against Human Cytomegalovirus Envelope Glycoprotein N - Pati, Sunil K. (American Society for Microbiology, 2012)
The human cytomegalovirus (HCMV) gM-gN complex is a major target of virus-neutralizing activity, and gN subtypes induce strain-specific antibodies. However, the biological significance of HCMV gN polymorphisms is not known. Neutralizing antibody responses against HCMV gN recombinant viruses were investigated at study entry in 80 healthy HCMV-seropositive women who were monitored for the appearance of new antibody specificities against linear strain-specific epitopes on glycoproteins gH and gB as evidence of HCMV reinfection. Neutralizing activity against all four gN recombinant viruses was seen in 74% of subjects, and 61% of subjects had strain-specific responses. Significantly fewer women (9/39 subjects [23%]) with serological evidence of reinfection had strain-specific neutralizing responses than the women without reinfection (21/41 subjects [51%]). Women with antibodies against at least one of the four linear gB and gH antigens at study entry had higher neutralizing titers against gN-1 (P = 0.006) and gN-2 (P = 0.007). Neutralizing titers of ≥400 against gN-3 (P = 0.043) and gN-4 (P = 0.049) at study entry were associated with longer times to serological evidence of reinfection. The findings demonstrate that HCMV gN elicits strain-specific neutralizing antibody responses and that broader anti-gN neutralizing activity may provide some protection from reinfection with a different virus strain.